2004
DOI: 10.1007/s00702-003-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides Rb1 and Rg1 effects on survival and neurite growth of MPP + -affected mesencephalic dopaminergic cells

Abstract: Ginsenosides Rb1 and Rg1 are the main active ingredients of Panax ginseng C.A. Meyer (Araliaceae). They appear to exert protection against ischaemia and anoxic damage in animal models, suggesting an antioxidative and cytoprotective role. In our study, primary cultures from embryonic mouse mesencephalon are applied to examine the effects of these two ginsenosides on neuritic growth of dopaminergic cells and their survival affected by 1-methyl-4-phenylpyridinium-iodide (MPP(+)). Ginsenoside Rb1 (at 10 microM) en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 18 publications
2
45
0
1
Order By: Relevance
“…The addition of Rb 1 (10 µM) results in 20% increased neurite lengths, a result which indicates growth stimulation or acceleration. As we could show in our previous study 53) MPP + concentrations of 1 µM decrease dopaminergic cell counts by about 40 %. Looking at neurite lengths of dopaminergic cells (Fig.…”
Section: Ginseng's Role In Parkinson's Disease Modelssupporting
confidence: 61%
See 1 more Smart Citation
“…The addition of Rb 1 (10 µM) results in 20% increased neurite lengths, a result which indicates growth stimulation or acceleration. As we could show in our previous study 53) MPP + concentrations of 1 µM decrease dopaminergic cell counts by about 40 %. Looking at neurite lengths of dopaminergic cells (Fig.…”
Section: Ginseng's Role In Parkinson's Disease Modelssupporting
confidence: 61%
“…Our studies have used primary dopaminergic cells 53) . Such nerve cell cultures can be prepared from embryonic mouse brains on gestation day 14.…”
Section: Ginseng's Role In Parkinson's Disease Modelsmentioning
confidence: 99%
“…In vitro studies showed that ginseng saponins enhanced neurite growth of dopaminergic SK-N-SH neuroblastoma cells (27). Recently, we demonstrated that ginsenosides Rb1 and Rg1 increased the survival of primary cultured dopaminergic cells and promoted their neuritic growth after exposure to either MPP + or glutamate (28,29 Although the processes and mechanisms underlying the neuroprotective effects of ginseng upon dopaminergic neurons remain to be elucidated, several reports demonstrate the inhibitory role of ginseng on MPP + uptake in dopaminergic neurons, the suppression of oxidative stress induced by autooxidation of dopamine, the attenuation of MPP + -induced apoptosis, and the potentiation of nerve growth factor (NGF). It has been shown that certain ginsenosides inhibit dopamine uptake into rat synaptosomes (31) and consequently ginseng could potentially provide protection against MPP + through blockade of its uptake by dopaminergic neurons (21).…”
Section: Ginseng's Role In Parkinson's Disease Modelsmentioning
confidence: 99%
“…Ginsenoside Rb1 is the main neuroprotective molecule of ginseng. It facilitates cholinergic function and increases synaptophysin levels in the hippocampus, potentiates the nerve growth factor (NGF)-mediated neurite outgrowth (14)(15)(16), reduces oxidative stress caused by hydrogen peroxide (17), and promotes neurite length and number after exposure to glutamate or hydrogen peroxide (18).…”
Section: Introductionmentioning
confidence: 99%